Pelatihan Penggunaan Teknologi Kecerdasan Buatan Untuk Guru Bahasa Inggris SMA di Wilayah Kabupaten Semarang - Mali, Yustinus Calvin Gai (Jurnal Pengabdian UntukMu NegeRI, 2026)
This community service program (PkM), in the form of teachers’ training, aims to introduce and demonstrate various artificial intelligence (AI) tools for teaching English as a Foreign Language (EFL). The PkM was held offline at State Senior High School 1 Getasan, Semarang Regency, Central Java, on Thursday, 25 September 2025, from 09.30 a.m. – 3.30 p.m. The participants of the training were 33 English teachers of various senior high schools in Semarang Regency. During the training, the author, who was also the speaker, introduced, demonstrated, and tried out some AI technology with the participants. The technology tools were: 1) Gliglish and 2) ChatGPT, which both can be used for practicing English conversations with AI. Another AI tool is 3) Google Translate, which can be used to practice English pronunciation and create an English-Indonesian dictionary. In addition to the AI technology, the author asked the participants to explore 4) British Council Websites for finding relevant English learning materials for their students. At the end of the session, the author asked participants to complete a Google Form to evaluate the session. Recommendations for following up on the current session were also presented in this paper.